Photo‐oxidation of poly(2, 6‐dimethyl‐1, 4‐phenylene oxide): A reinvestigation. Issue 14 (20th April 2017) - Pickett, James E.
ABSTRACT: Reinvestigation of poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) photodegradation at wavelengths > 290 nm shows that both methyl groups and aromatic rings are sites of oxidation with their relative rates dependent on exposure conditions, based on infrared spectroscopy. The methyl group loss is linear with exposure and apparently proceeds by direct abstraction of a benzylic hydrogen by oxygen. The aromatic ring loss and carbonyl growth in the IR spectra appear to be auto‐accelerating and seem to proceed by electron transfer to oxygen, either sensitized or through a direct reaction with oxygen, and recombination of the polymer radical cation and superoxide to result in oxygen addition to the ring. Molecular weight loss in solution occurs to a significant degree only in the presence of oxygen, even in the presence of a hydrogen‐donating solvent, indicating that aryl ether photolysis is not a major pathway. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2318–2331 Abstract : Poly(phenylene oxide) undergoes photo‐oxidation resulting in chain cleavage and yellowing. Purified, capped polymer degrades only slightly more slowly than as‐made, extruded polymer. At least two independent processes are at work: fast ring oxidation that appears to be sensitized by photodegradation products and slow methyl group oxidation that proceeds at a constant rate. Direct ether photolysis is at most a minor pathway.